ANALISIS PENGUKURAN KINERJA RUMAH SAKIT DENGAN PENDEKATAN BALANCED SCORECARD PADA RUMAH SAKIT DAERAH MADANI PALU - Parmita, Ririn (Katalogis, 2015)
This study aims to analyze the performance of a customer perspective, financial perspective, internal business perspective and learning and growth perspective. Respondents in this study for the customer's perspective is the patient or family as much as 97 people and for internal business perspective and learning and growth perspective is the Regional Hospital Madani employees 82 people, the sampling technique used is proportional random sampling method. Methods of data analysis in this research is to use the financial perspective by using financial ratio analysis, and for the customer perspective, internal business process and learning and growth perspective using frequency distribution data analysis. Results of performance measurement balanced scorecard at the Regional Hospital overall Madani reached a score of 0.8. The rating scale is based on the Regional Hospital Madani included in both categories despite the performance of each perspective is not maximized. Results of this study demonstrate and encourage the use of the balanced scorecard measurement of the organization with each organization to provide an overview of an organization's performance is more complete and kompherensif.